Construction of (3, 8)‐connected three‐dimensional cobalt(II) and copper(II) coordination polymers with 1, 3‐bis[(1, 2, 4‐triazol‐4‐yl)methyl]benzene and benzene‐1, 3, 5‐tricarboxylate ligands. Issue 7 (19th June 2019) - Zhang, Ya-Qian; Blatov, Vladislav A.; Lv, Xiu-Xiu; Tang, Ding-Yi; Qian, Lin-Lu; Li, Ke; Li, Bao-Long
Abstract : Two (3, 8)‐coordinated three‐dimensional networks based on a tetranuclear hydroxide cobalt(II) cluster or with a tetranuclear hydroxide copper(II) cluster, 1, 3‐bis[(1, 2, 4‐triazol‐4‐yl)methyl]benzene and benzene‐1, 3, 5‐tricarboxylate were synthesized. The compounds exhibit good photocatalytic degradation of the organic dyes methylene blue (MB) and rhodamine B (RhB) under visible‐light irradiation. Abstract : Coordination polymers (CPs) have been widely studied because of their diverse and adjustable topologies and wide‐ranging applications in luminescence, chemical sensors, magnetism, photocatalysis, gas adsorption and separation. In the present work, two coordination polymers, namely poly[(μ5 ‐benzene‐1, 3, 5‐tricarboxylato‐κ 6 O 1 : O 1′ : O 3 : O 3 : O 5, O 5′ ){μ3 ‐1, 3‐bis[(1, 2, 4‐triazol‐4‐yl)methyl]benzene‐κ 3 N : N ′: N ′′}di‐μ3 ‐hydroxido‐dicobalt(II)], [Co2 (C9 H3 O6 )(OH)(C12 H12 N6 )] n or [Co2 (btc)(OH)(mtrb)] n, (1), and poly[[diaquabis(μ3 ‐benzene‐1, 3, 5‐tricarboxylato‐κ 3 O 1 : O 3 : O 5 )bis{μ3 ‐1, 3‐bis[(1, 2, 4‐triazol‐4‐yl)methyl]benzene‐κ 3 N : N ′: N ′′}tetra‐μ3 ‐hydroxido‐tetracopper(II)] monohydrate], {[Cu4 (C9 H3 O6 )2 (OH)2 (C12 H12 N6 )2 (H2 O)2 ]·H2 O} n or {[Cu4 (btc)2 (OH)2 (mtrb)2 (H2 O)2 ]·H2 O} n, (2), were synthesized by the hydrothermal method using 1, 3‐bis[(1, 2, 4‐triazol‐4‐yl)methyl]benzene (mtrb) and benzene‐1, 3, 5‐tricarboxylate (btc 3− ). CP (1) exhibits a (3, 8)‐coordinated three‐dimensional (3D) network of the 3, 8T38 topological type, with a point symbol of {4, 5, 6}2 {4 2 ·5 6 ·6 16 ·7 2 ·8 2 }, based on the tetranuclear hydroxide cobalt(II) cluster [Co4 (μ3 ‐OH)2 ]. CP (2) shows a (3, 8)‐coordinatedtfz‐d topology, with a point symbol of {43 }2 {4 6 ·6 18 ·8 4 }, based on the tetranuclear hydroxide copper(II) cluster [Cu4 (μ3 ‐OH)2 ]. The different (3, 8)‐coordinated 3D networks based on tetranuclear hydroxide–metal clusters of (1) and (2) are controlled by the different central metal ions [Co II for (1) and Cu II for (2)]. The thermal stabilities and solid‐state optical diffuse‐reflection spectra were measured. The energy band gaps ( E g ) obtained for (1) and (2) were 2.72 and 2.29 eV, respectively. CPs (1) and (2) exhibit good photocatalytic degradation of the organic dyes methylene blue (MB) and rhodamine B (RhB) under visible‐light irradiation.